Community-based primary healthcare training for physiotherapy: Students' perceptions of a learning platform - Vijaya Misra; Nomzamo Chemane; Stacy Maddocks; Verusia Chetty (AOSIS, 2019)
Background: South Africa is faced with an overburdened public healthcare system and physiotherapists need to be equipped to address these challenges. Community-based primary healthcare clinical training (CBPHCT) offers physiotherapy students with learning opportunities to develop core competencies in order to address the needs of a disparate healthcare system. Objectives: To explore the experiences of physiotherapy students participating in a CBPHCT platform. Method: An explorative qualitative approach was adopted, using focus group discussions with final year physiotherapy students exposed to a year of CBPHCT. Data from the focus groups were transcribed and analysed using content analysis. Results: Four overarching themes were identified: prerequisite community-based primary healthcare competencies, positive factors associated with CBPHCT, negative factors associated with CBPHCT and recommendations. Conclusion: The CBPHCT experience was seen to present challenges to, and have benefits for, physiotherapy students. The students felt that communication between stakeholders, such as academic staff and hospital personnel, could be developed, while the lack of resources, such as Internet access, posed a barrier to learning. Students felt core competencies, such as professionalism of caring, were influenced by their exposure to the clinical personnel. Furthermore, they saw themselves as health advocates and felt there was mutual benefit from engagement with communities during their clinical placements. Recommendations included a review of physiotherapy curricula to prepare students for CBPHCT. Clinical implications: Community-based primary healthcare clinical training provides learning opportunities for undergraduate physiotherapy students to develop core competencies, such as health advocacy, necessary to address the unique needs of a disparate South African healthcare system.